The Potential Role of Iceland in Northern Europe's Protein Self-Sufficiency: Feasibility Study of Large-Scale Production of Spirulina in a Novel Energy-Food System. - Tzachor, Asaf; Richards, Catherine E; Smidt-Jensen, Asger; Skúlason, Arnar Þór; Ramel, Alfons; Geirsdóttir, Margrét (MDPI AG, 2023)
Europe is dependent on protein-rich crop imports to meet domestic food demand. This has moved the topic of sustainable protein self-sufficiency up the policy agenda. The current study assesses the feasibility of protein self-sufficiency in Iceland, and its capacity to meet Northern Europe's demand, based on industrial-scale cultivation of Spirulina in novel production units. Production units currently operating in Iceland, and laboratory-derived nutritional profile for the Spirulina cultivated, provide the basis for a theoretical protein self-sufficiency model. Integrating installed and potentially installed energy generation data, the model elaborates six production scale-up scenarios. Annual biomass produced is compared with recommended dietary allowance figures for protein and essential amino acids to determine whether Northern Europe's population demands can be met in 2030. Results show that Iceland could be protein self-sufficient under the most conservative scenario, with 20,925 tonnes of Spirulina produced using 15% of currently installed capacity. In a greater allocation of energy capacity used by heavy industry, Iceland could additionally meet the needs of Lithuania, or Latvia, Estonia, Jersey, Isle of Man, Guernsey, and Faroe Islands. Under the most ambitious scenario utilizing planned energy projects, Iceland could support itself plus Denmark, or Finland, or Norway, or Ireland with up to 242,366 tonnes of biomass. On a protein-per-protein basis, each kilogram of Spirulina consumed instead of beef could save 0.315 tonnes CO2-eq. Under the most ambitious scenario, this yields annual savings of 75.1 million tonnes CO2-eq or 7.3% of quarterly European greenhouse gas emissions. Finally, practicalities of production scale-up are discussed.